Illness Perceptions and Quality of Life in Patients with Non-Small-Cell Lung Cancer: A 3-Month Follow-Up Pilot Study - Vollmann, Manja (Patient Relat Outcome Meas, 2020)
PURPOSE: Examine illness perceptions, functional health and quality of life of lung cancer patients throughout chemotherapy treatment. PATIENTS AND METHODS: Longitudinal design with baseline measure 12 days after the first chemotherapy and follow-up measure 3 months later, where illness perceptions (BIPQ), functional health, and quality of life (EORTC QLQ-C-30) were measured. A total of 21 patients with non-small-cell lung cancer took part. Non-parametric testing was performed given the pilot nature of the study and the associated relatively small sample size. RESULTS: Small to medium changes in illness perceptions and functional health between the two measurement points were detected, with both becoming more positive. More negative illness perceptions at the beginning of the treatment were associated with less functioning and lower quality of life at both beginning and end of treatment. CONCLUSION: Addressing illness perceptions seems a clinically relevant approach in improving functioning and quality of life of patients with non-small-cell lung cancer.